Extraordinary Care for Extraordinary Conditions: Constructing Parental Care for Serious Mental Illness in Japan. - Rubinstein, Ellen B. (Culture, Medicine & Psychiatry, 2018)
This article presents an account of how Japanese parents in a family support group for mental illness constructed understandings of care for adult children with serious mental illness, primarily schizophrenia. I build from Janis H. Jenkins's research on the "extraordinary condition" of schizophrenia to discuss "extraordinary care," which parents practiced as a way to refute cultural and clinical beliefs about pathogenic families and degenerative diseases. Parents' accounts of extraordinary care revealed a reliance on biomedical knowledge to treat the symptoms of mental illness coupled with an ongoing determination to improve children's lives beyond what psychiatry could offer. Extraordinary care thus points to the therapeutic limits of biomedical psychiatry while also reinforcing the significance of social relations as families work toward recovery.